2001
DOI: 10.3354/dao045145
|View full text |Cite
|
Sign up to set email alerts
|

A model of salmon louse production in Norway: effects of increasing salmon production and public management measures

Abstract: Salmon lice Lepeophtheirus salmonis Krøyer have caused disease problems in farmed Atlantic salmon Salmo salar L. since the mid-1970s in Norway. High infection intensities and premature return of wild sea trout Salmo trutta L. were first reported in 1992. Later emaciated wild Atlantic salmon smolts carrying large amounts of lice have been observed both in fjords and offshore. The Norwegian Animal Health Authority regulations to control the problem, which came into operation in 1998, included compulsory louse le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 11 publications
(7 reference statements)
6
113
0
Order By: Relevance
“…The source of the sea lice causing the epizootics on juvenile salmonids in spring must be either wild salmonids that did not migrate offshore, escaped or feral farm fishes, salmon farms or non-salmonid wild hosts. Escaped farm fishes are a significant reservoir of lice in Norway in comparison with wild salmonids (Heuch & Mo 2001), but whether they may be a reservoir elsewhere is not clear.…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
“…The source of the sea lice causing the epizootics on juvenile salmonids in spring must be either wild salmonids that did not migrate offshore, escaped or feral farm fishes, salmon farms or non-salmonid wild hosts. Escaped farm fishes are a significant reservoir of lice in Norway in comparison with wild salmonids (Heuch & Mo 2001), but whether they may be a reservoir elsewhere is not clear.…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
“…For example, populations of farmed salmon (usually Atlantic salmon, Salmo salar) are orders of magnitude larger than sympatric wild salmonid populations in salmon farming regions of Norway, Scotland, Ireland, New Brunswick, and British Columbia (Heuch & Mo 2001, Butler 2002, Krko$ek 2009. In western North America, populations of the non-indigenous Pacific oyster Crassostrea gigas in aquaculture facilities dwarf the remnant and depleted populations of native Olympia oysters Ostrea lurida, the only native oyster in the region (McGraw 2009).…”
Section: Host Populations At Seamentioning
confidence: 99%
“…Heuch et al (2009) demonstrated that higher salinity in the outer fjord areas correlates with a higher sea louse infection at salmon farms in the Hardangerfjord. However, as noted by Heuch & Mo (2001) and further corroborated by Brooks (2005), local prevailing oceanographic conditions are important to the area-specific interaction between sea lice and salmon smolt, and it is not certain that similar spatial patterns will emerge in the other fjord systems. We strongly recommend that regional analysis of spawner density should be conducted in other similar areas, and especially in areas with lower concentrations of fish farms.…”
Section: Salmonmentioning
confidence: 99%
“…Consequently, the species are vulnerable to a series of anthropogenic stressors and many populations have declined or have become extinct in the last century (Parrish et al 1998). Aas et al (2011) considered river regulation and pollution as the most relevant threats to salmon and sea trout in freshwater, while overfishing and aquaculture related effects are considered to be highly relevant for sea survival (Heuch et al 2001;Costello 2006;Skaala et al 2006). Vøllestad et al (2009) examined two data sets on catches of salmon from Scottish and Norwegian rivers and concluded that in addition to temporal trends in catches in the different regions, there was also an indication of a strong local-scale effect (i.e.…”
Section: Introductionmentioning
confidence: 99%